Linear listing order and hierarchical classification: history, conflict, and use - Minelli, Alessandro (European Journal of Taxonomy, 2023)
Taxonomic criteria alone are not sufficient to determine a linear sequence for the arrangement of collection specimens according to a preferred classification or the linear sequence according to which taxa are best discussed in articles or books. The choice of methodology to obtain a linear sequence of taxa in agreement with a hierarchical classification has been little studied and remains controversial. In this article, I offer an historical background, before examining properties, use and limits of possible listing criteria. The result of a linearization effort depends on arbitrary choices with respect to two aspects of the hierarchical classification we intend to linearize. One is the order to be followed in listing the immediately subordinate members of a given taxon, the other is the choice of the sets of taxa to be linearized according to tradition, alphabetic order or other criterion. The example presented here, related to the “orders” of Hexapoda, demonstrates the need to specify very clearly the extent and composition of the uncollapsed classification backbone retained in the linearization procedure.